Annual Financial Statements - Report Of The Independent Auditors - N N/A (The Southern African Institute of Mining and Metallurgy, 2000)
To the members of The South African Institute of Mining and Metallurgy We have audited the annual financial statements set out on pages 239 to 245. These financial statements are the responsibility of the Institute?s Council. Our responsibility is to express an opinion on these financial statements based on our audit. Scope We have conducted our audit in accordance with statements of South African Auditing Standards. These standards require that we plan and perform the audit to obtain reasonable assurance that the financial statements are free of material misstatement. An audit includes: ?examining, on a test basis, evidence supporting the amounts and disclosures in the financial statements ?assessing the accounting principles used and significant estimates made by management ?evaluating the overall financial statement presentation. We believe that our audit provides a reasonable basis for our opinion. Audit opinion In our opinion, the financial statements fairly present, in all material respects, the financial position of the Institute at 30 June, 2000, and the results of its operations and cash flows for the year then ended in accordance with South African Statements of Generally Accepted Accounting Practice.